1993
DOI: 10.1161/01.cir.88.6.2565
|View full text |Cite
|
Sign up to set email alerts
|

Late reperfusion for acute myocardial infarction limits the dilatation of left ventricle without the reduction of infarct size.

Abstract: Late reperfusion appeared to prevent ventricular dilatation acute myocardial infarction independent of the limitation of infarct size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 56 publications
1
33
1
1
Order By: Relevance
“…The infarct sizes estimated from the peak MLC1 level were similar between the groups. These results are consistent with previous reports 24 of the open artery hypothesis that late reperfusion could prevent LV remodeling after the onset of AMI, whereas infarct size is not preserved.…”
Section: Possible Mechanisms Of Beneficial Effects Of Late Reperfusionsupporting
confidence: 93%
“…The infarct sizes estimated from the peak MLC1 level were similar between the groups. These results are consistent with previous reports 24 of the open artery hypothesis that late reperfusion could prevent LV remodeling after the onset of AMI, whereas infarct size is not preserved.…”
Section: Possible Mechanisms Of Beneficial Effects Of Late Reperfusionsupporting
confidence: 93%
“…26) Reperfusion prevents left ventricle dilatation, even if it is relatively delayed (achieved within > 4 to 6 hours). 27) In our study, statistically significant changes were found in group A patients only in the period between discharge and day 30 from randomisation. The EDD did not change significantly in groups B and C until the 6-month check-up.…”
Section: Discussionmentioning
confidence: 38%
“…24) It begins very early after MI, reaches a maximum rate within 14 days, and persists at a slower rate for at least 6-12 months, and probably longer. [24][25][26][27] Left ventricle end-diastolic dimension is an indicator of left ventricle remodelling. Both end-diastolic and end-systolic dimensions increase after myocardial infarction but, with reperfusion, the left ventricle dimension demonstrates a lower rate of increase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that infarct-related artery patency is an important determinant of ventricular remodeling after AMI. 19,20 In the current study, the incidence of TIMI grade 3 at follow-up did not differ between the 2 groups. In addition, it is noteworthy that the use of medications, such as nitrates 21 and ACEI, which might prevent ventricular remodeling after AMI, were similar between the 2 groups.…”
Section: Ventricular Functionmentioning
confidence: 42%